The use of the Interactive Learning Platform Quizizz in Enhancing Vocabulary Acquisition in English Language Teaching: A Literature Review Study - Dara Aprita; Johanes Sapri; Shima Asadi; Muhammad Qais Rezvani (Indonesian Journal of Pedagogy and Teacher Education, 2025)
Background: English vocabulary understanding remains a chronic challenge for EFL students in Indonesia, especially at the junior secondary level, where limited prior exposure and traditional rote-learning approaches frequently result in low motivation and low retention. Aims: This study aims to bring together empirical evidence on the efficacy of Quizizz, a gamified digital assessment instrument, in improving English vocabulary acquisition and involvement among EFL learners. Methods: A systematic literature review was undertaken in accordance with PRISMA standards. 20 peer-reviewed research (2019-2025) from Google Scholar, Scopus, and Sinta-indexed journals were thematically examined along six dimensions: vocabulary acquisition, motivation, anxiety reduction, usability, feedback, and implementation concerns. Result: Based to the findings, 85% of studies revealed higher motivation, 45% confirmed improved vocabulary retention (particularly in picture-word recognition), and 30% stated less language anxiety as a result of Quizizz's game-like, low-stakes design. However, 50% highlighted problems such as inconsistent internet, time constraints, and limited higher-order thinking activities. Conclusion: Quizizz is an appealing tool for vocabulary reinforcement and affective engagement in EFL settings, especially when integrated into communicative teaching methodologies and tailored to local infrastructure realities